Evolution of Law Relating to Liquidation of Company in Nepal: An Overview (Tribhuvan University Law Journal, 2025)
Company law deals with the matters between life and death of a company, i.e. incorporation, registration, audit, update and liquidation. Once liquidation of a company is accomplished, all the outstanding assets and liabilities are settled among its shareholders and creditors, and the firm loses its legal existence forever. The first legal provision on liquidation featured in the Nepal Company Kanoon of 1993 BS which included provisions on appointment of liquidator, his or her rights and duties and the conduction of liquidation process. Later, liquidation of solvent companies found mention in subsequent company laws also, such as the Companies Act 2007 BS, 2021 BS, 2053 BS, 2062 BS and also the incumbent Companies Act of 2063 BS.However, the liquidation of insolvent companies or involuntary liquidation found late entry into the Nepali company landscape, with the first and only Insolvency Act being enacted in 2063 BS together with the new Companies Act. However, the insolvency of natural persons (bankruptcy) has been regulated as back as in the Muluki Ain of 1910 BS. The current Insolvency Act, 2063 BS strictly concerns itself with corporate insolvency and provides for several key arrangements in this regards such as Commercial Bench at the concerned High Court, insolvency practitioners, inquiry officer, prohibition on commencing insolvency proceedings without a court order, appointment of inquiry officer, creation of an Insolvency Administration Office, committee of creditors, company restructuring program, functions, duties and powers of insolvency practitioner, etc. Though the present Insolvency Act adopts a “one law, two systems” approach, including both the regimes of liquidation and restructuring, it lags behind in addressing the latest developments in insolvency affairs marking today’s world.